Evaluasi Program Pemberdayaan Masyarakat Plus (Prodamas Plus) dalam Meningkatkan Pendapatan Masyarakat di Kelurahan Burengan Kota Kediri - Daniel Wahyu Triatmojo; Bayu Priambodo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to evaluate and describe the Prodamas Plus program in improving community income in Burengan Village, Kediri City. Using a descriptive qualitative approach, the research assesses the program based on six evaluation criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The findings indicate that Prodamas Plus is effective in fulfilling basic community needs, particularly in infrastructure development and public facilities, yet it has not optimally improved community income due to limited community capacity and the lack of sustainable post-training assistance. In terms of efficiency, program governance is well-structured, but implementation in the field is constrained by tight execution timelines and high administrative burdens. Program adequacy is strong at the basic level but remains insufficient in economic empowerment efforts. Equity in access to development has been achieved, although equality in economic outcomes is still uneven among residents. The program demonstrates high responsiveness through various public participation channels and service mechanisms that accommodate community aspirations. Accuracy is reflected in the program’s alignment with infrastructure needs but is not yet fully evident in generating significant income improvements. Overall, Prodamas Plus has successfully enhanced environmental quality and public services; however, stronger economic empowerment strategies are required to ensure more optimal and sustainable contributions to the income of Burengan residents.